Consideration of the religious factor in strategic planning documents of national security of the Republic of Belarus - Vaitsiakhovich, Vyacheslav A. (Journal of the Belarusian State University. Law, 2023)
The author of the article examines the problem of ensuring religious security in national security theory context. The analysis of the current state of the religious sphere of the Republic of Belarus was carried out, aspects of religious factor consideration in the doctrinal documents of strategic planning in the field of national security are reflected. Prioritised theoretical and practical aspects of religious security study as an independent type of national security are identified.
Keywords: religion; state; security; denomination; community; religious sphere; interfaith relations